2016
DOI: 10.1063/1.4967959
|View full text |Cite
|
Sign up to set email alerts
|

Spooky correlations and unusual van der Waals forces between gapless and near-gapless molecules

Abstract: We consider the zero-temperature van der Waals interaction between two molecules, each of which has a zero or near-zero electronic gap between a groundstate and the first excited state, using a toy model molecule ( equilateral H 3 ) as an example. We show that the van der Waals energy between two groundstate molecules falls off as D −3 instead of the usual D −6 dependence, when the molecules are separated by distance D. We show that this is caused by perfect "spooky" correlation between the two fluctuating ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…As a result, a wide range of empirical correction schemes are commonly added to GGA calculations so as to produce a realistic description of the critical interactions ( 24 , 25 ). The vdW dispersion interactions described by these schemes typically involve sums over interatomic interactions, each described by the London force ( 21 , 26 28 ), with only small corrections. Related variants include replacing the atomic sums by electron-density integrals.…”
mentioning
confidence: 99%
“…As a result, a wide range of empirical correction schemes are commonly added to GGA calculations so as to produce a realistic description of the critical interactions ( 24 , 25 ). The vdW dispersion interactions described by these schemes typically involve sums over interatomic interactions, each described by the London force ( 21 , 26 28 ), with only small corrections. Related variants include replacing the atomic sums by electron-density integrals.…”
mentioning
confidence: 99%
“…Comparing eqs 13 and 9, we find that we can make our Ansatz give the correct long-wavelength response provided that we choose the constant B in χ 0 Ansatz such that (14) The factor of 1/R on the right side of eq 14 comes from the conversion between continuous "()" and discrete "[ ]" Fourier transforms. Putting eqs 9 and 13 into eq 14 gives (15) So, eq 16 becomes (16) This agrees with the known 1D metallic response when q → 0 but is not necessarily correct for larger q. However, the principal "Type-C" effects of metallicity on dispersion interactions come from the long-wavelength metallic response, and so, the present model should be appropriate.…”
Section: ■ General Form Of the Mbd + C Approachmentioning
confidence: 57%
“…In low-dimensional metals, this gives rise to gapless plasmon excitations that are not captured by the MBD theory. Coupling between these plasmons results in unusual power law decays of the dispersion interaction between low-dimensional metals, sometimes termed “Type-C” dispersion interactions. Similar anomalous dispersion interactions have been proposed in a variety of other cases with a small or zero electronic energy gap. The Type-C interactions are not captured by standard MBD calculations. ,, …”
Section: Introductionmentioning
confidence: 93%
“…Recent studies have suggested that Type-B non-additivity can also be interpreted as a manifestation of electric many-body effects. 17 Type-C non-additivity is observed in low-dimensional nanostructures or metallic systems, where long-range charge ŕuctuations result in dispersion interactions with non-standard power laws, with a smaller magnitude of the exponent of R. 18 Semiclassical models with pairwise expressions, such as Eq. ( 1), including Grimme's DFT+Dn (n = 1, 2, 3, 4) schemes, [19][20][21][22][23] Tkatchenko and Scheffler (TS) method, 13 the exchange-hole dipole moment (XDM) method by Becke and Johnson, 12,24,25 and the localresponse dispersion (LRD) model by Sato and Nakai, [26][27][28] consider type-A non-additive dispersion interactions.…”
Section: Introductionmentioning
confidence: 99%